Assessment of a standard treatment protocol on visual outcome following presumed bacterial endophthalmitis. Issue 9 (1st September 1997) - Okhravi, N; Towler, H M A; Hykin, P; Matheson, M; Lightman, S
Abstract : AIMS: The aim of this prospective study was, firstly, to judge the effect of early aggressive treatment with a standardised regimen of high dose broad spectrum intraocular and systemic antibiotics on visual outcome and, secondly, to assess the sensitivity of isolated organisms to the treatment regimen utilised. METHODS: Thirty two consecutive patients presenting with presumed bacterial endophthalmitis were treated and completed follow up. In every case, intraocular sampling was undertaken and treatment with intraocular vancomycin, amikacin, and systemic ciprofloxacin was commenced immediately, followed by systemic steroids 1 day later. RESULTS: In 69% of patients vision improved with 47% achieving a final visual acuity of 6/36 or better and 31% achieving 6/12 or better. Of the intraocular samples taken from post-surgical and post-traumatic cases, 10/27 (37%) and 3/5 (60%) were culture positive, respectively. All the bacteria isolated were sensitive to at least one of the three antibiotics used. CONCLUSIONS: The study demonstrated that the combination of vancomycin, amikacin, and ciprofloxacin is adequate as a standard regimen for the treatment of most patients with suspected bacterial endophthalmitis. The prognosis for a good visual outcome, however, remains poor with 15/27 (55%) post-surgical and 2/5 (40%) post-traumatic cases achieving a final acuity of 6/60 or less.